2014
DOI: 10.1016/j.virol.2014.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Escape from neutralization by the respiratory syncytial virus-specific neutralizing monoclonal antibody palivizumab is driven by changes in on-rate of binding to the fusion protein

Abstract: The role of binding kinetics in determining neutralizing potency for antiviral antibodies is poorly understood. While it is believed that increased steady-state affinity correlates positively with increased virus-neutralizing activity, the relationship between association or dissociation rate and neutralization potency is unclear. We investigated the effect of naturally-occurring antibody resistance mutations in the RSV F protein on the kinetics of binding to palivizumab. Escape from palivizumab-mediated neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 28 publications
3
26
0
2
Order By: Relevance
“…Despite relatively rare usage of the antibody and the highly conserved nature of its viral protein target, resistance has been reported due to variations in the fusion protein binding site. [64][65][66][67][68] One study 69 investigated the human monoclonal antibody MPE8, which cross-neutralises respiratory syncytial virus and human metapneumovirus by binding to two highly conserved anti-parallel β-strands on the pre-fusion viral fusion protein. The investigators found naturally occurring antibodies with this same target specificity in some patient serum samples, and therefore proposed this pre-fusion viral fusion protein as a potential vaccine candidate.…”
Section: Antiviral Drug and Vaccine Developmentmentioning
confidence: 99%
“…Despite relatively rare usage of the antibody and the highly conserved nature of its viral protein target, resistance has been reported due to variations in the fusion protein binding site. [64][65][66][67][68] One study 69 investigated the human monoclonal antibody MPE8, which cross-neutralises respiratory syncytial virus and human metapneumovirus by binding to two highly conserved anti-parallel β-strands on the pre-fusion viral fusion protein. The investigators found naturally occurring antibodies with this same target specificity in some patient serum samples, and therefore proposed this pre-fusion viral fusion protein as a potential vaccine candidate.…”
Section: Antiviral Drug and Vaccine Developmentmentioning
confidence: 99%
“…As an example, Bates et al [30] used this methodology to explore the role of binding kinetics on the neutralizing potency of the MAb palivizumab against respiratory syncytial virus (RSV). Investigating naturally occurring mutations of the RSV F protein, the target of palivizumab, indicated that while reduction of k on resulted in increased escape from MAb-mediated neutralization of RSV, changes in k off did not significantly affect neutralizing activity.…”
Section: In Vitro Evaluations Of Monoclonal Antibody Bindingmentioning
confidence: 99%
“…One of these substitutions, Asn268Ile, may affect the neutralization of HRSV (Bates et al, 2014), whereas other substitutions may not have such an effect (Bates et al, 2014;Schickli et al, 2015).…”
mentioning
confidence: 99%
“…Thus, nonsynonymous mutations, such as Asn268Ile, that map to the Palivizumab epitope may influence the effectiveness of this drug (Bates et al, 2014). However, this mutant, which occurs in GA5, has rarely been detected globally (Trento et al, 2015) and additional surveillance may be needed to detect this mutant in the future.…”
mentioning
confidence: 99%